The raw truth about paper mills - Christopher, Jana (FEBS letters, 2021)
In 2018, the community first observed scientific papers in the biomedical literature that seemed to display systematically fabricated data, pointing to the existence of paper mills: unofficial, potentially illegal organizations selling fake scientific manuscripts. In the present article, we share relevant information specifically about the ‘raw data’ associated with paper mill manuscripts. If a submitted manuscript displays clear indicators of potential paper mill involvement, we found that the raw data at close inspection often raise doubts about their authenticity. In the absence of real data, paper mills may need to fabricate raw data images when responding to requests from journals. Given the necessity to streamline production of fake manuscripts, the alleged raw data might be created using templates. Some potential methods for generating fake Western blot images are discussed. Paying close attention to image data, including graphs, diagrams, plots and tables, ideally at pre-publication stage, can clearly help prevent publication of incorrect and fabricated information.